The centrifugal spinning of vitamin doped natural gum fibers for skin regeneration. (15th October 2022) - Rihova, Martina; Lepcio, Petr; Cicmancova, Veronika; Frumarova, Bozena; Hromadko, Ludek; Bureš, Filip; Vojtova, Lucy; Macak, Jan M.
Abstract: The study investigates the use of fiber carriers, based on biopolymeric gums as potential candidates for cosmetic and dermatological applications, in particular for skin regeneration. Gum arabic (GA), xanthan gum (XA), and gum karaya (GK) were used as the main gum materials for the fibers, which were prepared by centrifugal spinning from an aqueous solution. These solutions of different mass gum ratios were blended with poly (ethylene oxide) (PEO) for better spinnability. Finally, vitamins E and C were added to selected solutions of gums. The resulting fibers were extensively investigated. The morphology and structure of all fibers were investigated by scanning electron microscopy and Fourier transformed infrared spectroscopy. Most importantly, they were characterized by the release of vitamin E loaded in the fibers using UV-VIS spectroscopy. The presentation will show that the newly prepared fibers from GA and PEO represent a very promising material for cosmetic and dermatologic applications. Graphical abstract: Unlabelled Image